Correction to: Family history assessment significantly enhances delivery of precision medicine in the genomics era (Genome Medicine, (2021), 13, 1, (3), 10.1186/s13073-020-00819-1) - Bylstra, Yasmin (BioMed Central Ltd, 2022)
10.1186/s13073-021-00916-9